Exopeptidases and gingipains in Porphyromonas gingivalis as prerequisites for its amino acid metabolism - Takayuki K. Nemoto; Yuko Ohara-Nemoto (Elsevier, 2016)
Porphyromonas gingivalis, an asaccharolytic bacterium, utilizes amino acids as energy and carbon sources. Since amino acids are incorporated into the bacterial cells mainly as di- and tri-peptides, exopeptidases including dipeptidyl-peptidase (DPP) and tripeptidyl-peptidase are considered to be prerequisite components for their metabolism. We recently discovered DPP11, DPP5, and acylpeptidyl oligopeptidase in addition to previously reported DPP4, DPP7, and prolyl tripeptidyl peptidase A. DPP11 is a novel enzyme specific for acidic P1 residues (Asp and Glu) and distributed ubiquitously in eubacteria, while DPP5 is preferential for the hydrophobic P1 residue and the first entity identified in prokaryotes. Recently, acylpeptidyl oligopeptidase with a preference for hydrophobic P1 residues was found to release N-terminally blocked di- and tri-peptides. Furthermore, we also demonstrated that gingipains R and K contribute to P1-basic dipeptide production. These observations implicate that most, if not all, combinations of di- and tri-peptides are produced from extracellular oligopeptides even with an N-terminal modification. Here, we review P. gingivalis exopeptidases mainly in regard to their enzymatic characteristics. These exopeptidases with various substrate specificities benefit P. gingivalis for obtaining energy and carbon sources from the nutritionally limited subgingival environment.